Avaliação in vivo e in vitro de terapias de uso em consultório para o tratamento da hipersensibilidade dentinária - Osmari, Deise (2011)
Dentinal hypersensitivity (DH) is a frequent clinical situation that is characterized by discomfort with pain ranging from slight to unbearable and it requires the professional to choose the appropriate therapy. Therefore, the aim of this study was to perform a clinical and morphological assessment of four in office therapies used for treating DH. The desensitizing therapies assessed were as follows: G1: fluoridated varnish (Control Group); G2: potassium oxalate; G3: hybridization with an adhesive system; G4: high-power diode laser. Twenty patients participated in the randomized, double-blind, controlled and split-mouth clinical study, each patient with 1 eligible tooth in each quadrant. Pain was measured using the Visual Analog Scale (VAS) after evaporative stimulus before the beginning of treatment, soon after the procedure and 15, 30 and 60 days after each application. The values of VAS immediately after the therapies, as well as after 15, 30 and 60 days, were compared to baseline values by the Wilcoxon test (non-parametric paired data) (α=0.05). The variation (Δ) in the VAS after each experimental group (VAS x days VAS baseline) was compared among the four experimental groups by ANOVA, following the Tukey s post hoc test (α =0.05). Fifteen dentin blocks (n=3) were obtained from the cervical third of vestibular faces of human pre-molar teeth for morphological analysis. Enamel was removed to expose dentin surface, polished with silicon carbide abrasive papers, and etched with 6% citric acid for 2 minutes. After therapies, the specimens were fractured in the buccolingual direction and prepared for analysis under Scanning Electron Microscope. The specimens were analyzed qualitatively both from the view of the buccal surface view and fractured surface. The variation of VAS immediately after therapies, subtracting the baseline value of VAS, differed among the groups. The highest value was found in G1 (fluoridated varnish) and the lowest value in G3 (adhesive system). With regard to VAS, no statistically significant differences among the therapies were found after the time intervals that corresponded to the assessments after 15, 30 and 60 days. In the group without treatment, etching removed the smear layer and exposed the dentinal tubules. A film on the surface with infiltration of varnish plugs into the tubules was found in the fluoridated varnish group. The oxalate group presented partial occlusion of the tubules with formation of crystals inside them. The tubules in the adhesive system group were obliterated by the formation of hybrid layer and a mechanical barrier on the surface. The high-power diode laser altered dentin superficially during melting and re-solidification, which partially occluded the tubules. All treatments were effective in reducing DH within the 60-day period and all desensitizing agents have shown the ability to modify the dentin surface by partially or completely occluding the dentinal tubules.